2010
DOI: 10.1089/hum.2008.089
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Human Blood Group A Antigen Expression on Mouse Cells, Using Lentiviral Gene Transduction

Abstract: The ABO histo-blood group system is the most important antigen system in transplantation medicine, yet no small animal model of the ABO system exists. To determine the feasibility of developing a murine model, we previously subcloned the human a-1,2-fucosyltransferase (H-transferase, EC 2.4.1.69) cDNA and the human a-1,3-Nacetylgalactosaminyltransferase (A-transferase, EC 2.4.1.40) cDNA into lentiviral vectors to study their ability to induce human histo-blood group A antigen expression on mouse cells. Herein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Although it is not yet clear which type of ABO antibody (IgM or IgG) is clinically more important in ABO‐i KT, our findings suggest that, unlike anti‐HLA antibodies, IgM anti‐ABO antibodies may have an important influence on AMR. This is in line with key studies that observed deposition of IgM and complement using immunohistochemical studies in hyperacutely rejected ABO‐i kidney grafts, as well as ABO‐specific IgM‐induced cytolysis in vitro and graft injury in vivo …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although it is not yet clear which type of ABO antibody (IgM or IgG) is clinically more important in ABO‐i KT, our findings suggest that, unlike anti‐HLA antibodies, IgM anti‐ABO antibodies may have an important influence on AMR. This is in line with key studies that observed deposition of IgM and complement using immunohistochemical studies in hyperacutely rejected ABO‐i kidney grafts, as well as ABO‐specific IgM‐induced cytolysis in vitro and graft injury in vivo …”
Section: Discussionsupporting
confidence: 90%
“…This is in line with key studies that observed deposition of IgM and complement using immunohistochemical studies in hyperacutely rejected ABO-i kidney grafts, 2 as well as ABO-specific IgM-induced cytolysis in vitro 32 and graft injury in vivo. 33 The molecular characteristics of ABO antigens are different from those of HLA antigens, as they are carbohydratebased and protein-based antigens, respectively. The antibody response against nonprotein antigens, such as polysaccharides and lipids, primarily relies on IgM production.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it also raised the intriguing possibility that the choice of specific glycans contributes to species specificity. In support of this, no binding of MNV-1 to available synthetic HBGA has so far been observed (13) despite the ability of MNV RNA to replicate in human cells (60), and the human ABO HBGA system, which is pivotal for human norovirus infection, does not exist in mice or any other small animal model (16).…”
Section: Discussionmentioning
confidence: 89%
“…Investigation of levels of antibodies against donor blood groups and B-cell responses has suggested that decreased production of donor-specific anti-blood group antibodies can be detected in graft recipients and the suggestion has been made that perhaps this decrease explains the well-being of ABO-incompatible kidney transplants. 55,56 However, the general experience has been that at least some recipients of ABO-incompatible kidney transplants produce substantial amounts of antibody against the donor antigen and the preponderance of ABO-incompatible transplants contain deposits of C4d, in the absence of impaired function and consistent with ongoing binding of anti-donor antibodies. [57][58][59] Even more to the point, the extent of antibody rebound after the first weeks appears to have little or no impact on the long-term outcome ( Figure 5).…”
Section: Chang E S In Antibody In Abo -In Compatib Le Tr An S Pl Anmentioning
confidence: 99%